Quantifying neptunium oxidation states in nitric acid through spectroelectrochemistry and chemometrics - Sadergaski, Luke R.; Andrews, Hunter B.; Gilson, Sara E.; Parkison, Adam J. (Frontiers in Nuclear Engineering, 2023)
has been authored by UT-Battelle LLC under contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan).